Optimum income taxation when earnings are imperfectly correlated with productivity - Bevan, D (University of Oxford, 2002)
Probably the most enduring result in the theory of optimum income taxation is that, for a sufficiently thin upper tail to the skill distribution, the marginal tax rate should fall rather than rise with income. This paper shows that this result is highly sensitive to a very strong informational assumption, namely that earnings exactly reflect a worker's contribution to output. While the formal structure of the optimum problem is altered only slightly when earnings are allowed to be less than perfectly correlated with productivity, the shape of the optimum schedule is very sensitive to this relaxation. For high but imperfect correlation, optimum schedules look rather like those traditionally chosen by governments, with the marginal rate rising over high incomes and possibly U-shaped over the whole distribution.